Heterogeneity of the determinants of euro-area sovereign bond spreads; what does it tell us about financial stability? - Georgoutsos, Dimitris A.; Migiakis, Petros M. (Journal of Banking & Finance, 2013)
In this paper, we assess the movements of euro area sovereign bond yield spreads vis-à-vis the German Bund as processes specified across different levels of volatility and subject to movements in asset prices and economic conditions. The determinants we use are grouped into domestic and euro-area aggregates, thus allowing us to derive results on their relative explanatory power and compare them across time and the spectrum of countries. We find that volatility influences the deterministic processes of the euro area sovereign spreads and that identical determinants have effects on spreads that vary considerably across countries. Furthermore, we find that variables reflecting investment confidence conditions and perceptions for the upcoming economic activity are significant determinants and their significance remains, to a large extent, even when controlling for fiscal variables.